After innocence: Perceptions of individuals who have been wrongfully convicted. (17th May 2013) - Clow, Kimberley A.; Leach, Amy‐May
<x xml:space="preserve">Abstract</x> Purpose Although it is easy to assume that individuals who have been wrongfully convicted are stigmatized, research has not systematically examined this issue. This research compares perceptions of individuals who have been wrongfully convicted to perceptions of offenders to investigate the stigma that wrongfully convicted persons report. Method Participants were randomly assigned to complete surveys regarding their attitudes, stereotypes, and discrimination tendencies towards one of three different groups: individuals who were wrongfully convicted of a crime, actual offenders, or people in general (control). Results Results suggested contemptuous prejudice towards offenders and wrongfully convicted persons. In comparison to the control group, individuals who had been wrongfully convicted were stereotyped more negatively, elicited more negative emotions, and were held at a greater social distance. Although participants did report greater pity for wrongfully convicted persons than others, this pity did not translate into greater assistance or support. Conclusions Perceptions of wrongfully convicted persons appear similar to negative, stigmatized views of offenders. Individuals faced stigma and discrimination even after exoneration.